Surface Modified Mesostructured Iron Oxyhydroxide: Synthesis, Ecotoxicity, and Application - Choi, Jae-Woo; Mahendran, Basuvaraj; Chung, Seung-Gun; Kim, Song-Bae; Lee, Sang-Hyup (WATER ENVIRONMENT FEDERATION, 2014)
Mesoporous iron oxide, particularly amine-functionalized FeOx and FeOx, was investigated for the removal of toxic heavy metal anions of arsenic and chromium from an aqueous solution. As a control experiment for these toxic compounds, adsorption tests were also performed on Fe3O4 as their counterpart bulk chemical. The mesostructures were confirmed by X-ray diffraction (XRD), Brunauer-Emmett- Teller (BET) and transmission electron microscopy (TEM). In addition, we prepared stock suspensions of meso-FeOx, amine-functionalized meso-FeOx and Fe3O4 particles, and compared their acute toxicity against Daphnia magna. The 24 h-EC50 values of the amine-functionalized meso-FeOx, meso-FeOx and Fe particle suspensions used in this study were 1682, 2549 and 95 mg/L, respectively. Organism toxicity caused by spills of adsorbents can be negated when the amine-functionalized meso-FeOx, up to 1500 mg/L, is used as the adsorbent for heavy metal treatment. The adsorption of arsenic and chromium by the three adsorbents were examined, and different adsorption models were used to describe the equilibrium and kinetic data. The amine-functionalized meso-FeOx adsorbent was found to give the maximum adsorption capacities for arsenic and chromium (33.51 and 25.05 mg/g, respectively). This research gives promising results for the application of modified meso-FeOx as an adsorbent of toxic heavy metal anions from aqueous solutions.